2007
DOI: 10.1051/parasite/2007144329
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the hepatic lesions experimentally induced in hamsters byEntamoeba disparandE. histolytica

Abstract: Summary :Evolution of experimental hepatic lesions produced in hamsters with Entamoeba histolytica and E. dispar was evaluated quantitatively and qualitatively through morphometry and immunohistochemistry. Animals infected with E. dispar developed hepatic lesions quantitatively and qualitatively similar to those produced by E. histolytica on the first three days of infection. On the 6 th and 8 th days of infection, E. histolytica produced larger tissue damage than E. dispar. A gradual decrease was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…In accordance, no significant differences in the extension of the necrotic area were observed in livers from hamsters inoculated with E. histolytica or E. dispar ( E. histolytica : 5.2 × 10 5 ± 7.2 × 10 5 ; E. dispar : 3.1 × 10 6 ± 2.7 × 10 6 ; p > 0.05). The data corresponding to the number of trophozoites and extension of the necrotic areas after 24, 48, 72, 144, and 192 h of infection were collected and analyzed previously and they were used in the present study [7]. Neither macro- nor microscopic lesions were observed in animals inoculated with E. histolytica or E. dispar flora.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance, no significant differences in the extension of the necrotic area were observed in livers from hamsters inoculated with E. histolytica or E. dispar ( E. histolytica : 5.2 × 10 5 ± 7.2 × 10 5 ; E. dispar : 3.1 × 10 6 ± 2.7 × 10 6 ; p > 0.05). The data corresponding to the number of trophozoites and extension of the necrotic areas after 24, 48, 72, 144, and 192 h of infection were collected and analyzed previously and they were used in the present study [7]. Neither macro- nor microscopic lesions were observed in animals inoculated with E. histolytica or E. dispar flora.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Costa et al . reported that the number of trophozoites increased in livers of hamsters infected with both strains at 24 h of inoculation, suggesting that the complement and antibodies actions were not able to completely eliminate the trophozoites [7]. As a consequence, this fact could select subpopulations of resistant parasites and contribute to the development of hepatic abscesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holzer, Sommerville & Wootten (2003) described similar remarks for Sphaerospora truttae stages present within macrophages. The mechanisms related to the progression of the lesion are unknown, but some authors suggested that the destruction of E. histolytica trophozoites could promote the consequent release of toxic products and/or enzymes that would contribute to the increase of necrosis and stimulate the development of the granuloma (Rivero-Nava et al 2002;Costa et al 2007). Costa et al 2010 pointed out the induction of apoptosis by E. histolytica, through direct activation of the host cells distal apoptotic machinery.…”
Section: Parasite Distribution Within the Hostmentioning
confidence: 99%
“…12 In addition, a gradual decrease was observed in the number of trophozoites in the course of infection. The decrease of trophozoites number associated with progressive increase of necrosis during inflammatory kinetics suggested that trophozoites destruction could promote the consequent release of toxic products that would contribute to the increase of necrosis.…”
Section: Introductionmentioning
confidence: 99%